Contribution of social responsibility to sustainable development goals in the costa rican family business: a case study - Mora-Ortega, Tania (2025)
Through a case study, the study aims to identify the Social Responsibility activities carried out by six Costa Rican family businesses to determine their contribution to the Sustainable Development Goals of the UN Agenda 2030 (specifically objective 3- health and well-being, 4- education quality, 5- gender equality and finally objective 8- decent work and economic growth). The research was developed through in-depth interviews with six Costa Rican family businesses. The results obtained indicate that the Social Responsibility practices implemented by the companies under study can contribute significantly to the achievement of SDG 3; 4; 5 and 8. Likewise, the results open opportunities for new lines of research on these topics.